Phenotypic and molecular characterization of industrial purpose cassava accessions with potential for adaptation to the conditions of Cerrado of Central Brazil Caracterização fenotípica e molecular de acessos de mandioca de indústria com potencial de adaptação às condições do Cerrado do Brasil Central - Marilia Santos Silva; Kenia Graciele da Fonseca; Graciele Bellon; Fabio Gelape Faleiro; Josefino de Freitas Fialho; Eduardo Alano Vieira; Silvana Vieira de Paula-Moraes; Luiz Joaquim Castelo Branco Carvalho (Semina: Ciências Agrárias, 2013)
The aim of the present work was to characterize and estimate the genetic variability among industrial purpose cassava accessions, with potential for adaptation to the conditions of Cerrado of Central Brazil, by means of quantitative and qualitative characters, and molecular markers through isolated and joint analysis, as well as to establish the correlation among the estimated indexes obtained by each used methodology. Sixteen industrial purpose cassava accessions with potential for adaptation to the conditions of Cerrado of Central Brazil were evaluated in field conditions in terms of 11 quantitative characters and 33 qualitative characters, in an experiment carried out at Embrapa Cerrados. The accessions were also evaluated through RAPD markers in laboratorial conditions. Afterwards, the matrices of genetic dissimilarity/distance among the accessions were estimated through qualitative characters, quantitative characters and molecular markers, besides through the joint analysis of the obtained data. Moreover, the association among the matrices was estimated. The results revealed existence of high variability among the accessions in terms of quantitative, qualitative and molecular characters evaluated. The only significant correlations found were between (i) the dissimilarity matrix estimated through joint analysis and the dissimilarity matrix estimated through qualitative data (r = 0,52); and (ii) the dissimilarity matrix estimated through joint analysis and the dissimilarity matrix estimated through molecular markers (r = 0,75). The weak association between these measures indicated that the best strategy to guide conservation actions and use of cassava industry germplasm is through studies of genetic divergence by the use of molecular markers, qualitative and quantitative traits in a joint and complementary way. O objetivo do trabalho foi caracterizar e estimar a variabilidade genética entre acessos de mandioca de indústria, com potencial de adaptação às condições do Cerrado do Brasil Central, por meio de caracteres quantitativos, qualitativos e marcadores moleculares de forma isolada e conjunta, bem como estimar a correlação entre as estimativas obtidas com base em cada grupo de caracteres. Dezesseis acessos de mandioca de indústria com potencial de adaptação às condições do Cerrado do Brasil Central foram avaliados a campo quanto a 11 caracteres quantitativos e 33 caracteres qualitativos, em experimento conduzido na Embrapa Cerrados. Os acessos foram também avaliados quanto a marcadores RAPD em laboratório. Posteriormente, foram estimadas as matrizes de dissimilaridade/distância genética entre os acessos por meio dos caracteres qualitativos, quantitativos e marcadores moleculares e pela análise conjunta dos dados. Além disso, foi estimada a correlação entre as matrizes. No grupo de acessos de indústria avaliados existe ampla variabilidade quanto aos caracteres quantitativos, qualitativos e moleculares aferidos. As únicas correlações significativas encontradas foram entre (i) a matriz de dissimilaridade estimada por meio da análise conjunta e a matriz de dissimilaridade estimada por meio de dados qualitativos (r = 0,52) e; (ii) a matriz de dissimilaridade estimada por meio da análise conjunta e a matriz de dissimilaridade estimada por meio de marcadores moleculares (r= 0,75). A fraca associação entre essas medidas indicou que a melhor estratégia para orientar ações de conservação e uso de germoplasma de mandioca de indústria é por meio de estudos de divergência genética com o emprego de marcadores moleculares, caracteres qualitativos e caracteres quantitativos de forma conjunta e complementar.